2012
DOI: 10.2527/jas.2010-3747
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic selenium supplementation on growth performance, carcass measurements, tissue selenium concentrations, characteristics of reproductive organs, and testis gene expression profiles in boars1

Abstract: The objective was to compare growth and physiological responses in boars fed diets supplemented with organic or inorganic sources of Se. At weaning, crossbred boars (n = 117; 8.3 kg of BW) were placed in nursery pens (3 boars/pen) and assigned within BW blocks to receive on an ad libitum basis 1 of 3 dietary treatments: I) basal diets with no supplemental Se (controls), II) basal diets supplemented with 0.3 mg/kg of organic Se, and, III) basal diets supplemented with 0.3 mg/kg of sodium selenite (13 pens/dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
7
9
0
Order By: Relevance
“…Selenium concentrations in plasma and tissues were influenced by both Se sources and levels. These results agreed with previous research with pigs (Mahan and Parrett, 1996;Mateo et al, 2007;Speight et al, 2012) and even on other species such as poultry (Juniper et al, 2011;Briens et al, 2013), cattle (Juniper et al, 2008), lamb (Qin et al, 2007), and sheep (Davis et al, 2008). The Se concentrations in plasma and liver were effectively increased when pigs were fed diets supplemented with Se, regardless of the source, in comparison with pigs receiving the unsupplemented control diet.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Selenium concentrations in plasma and tissues were influenced by both Se sources and levels. These results agreed with previous research with pigs (Mahan and Parrett, 1996;Mateo et al, 2007;Speight et al, 2012) and even on other species such as poultry (Juniper et al, 2011;Briens et al, 2013), cattle (Juniper et al, 2008), lamb (Qin et al, 2007), and sheep (Davis et al, 2008). The Se concentrations in plasma and liver were effectively increased when pigs were fed diets supplemented with Se, regardless of the source, in comparison with pigs receiving the unsupplemented control diet.…”
Section: Discussionsupporting
confidence: 91%
“…In pigs, as well as in other domestic animal species, Se metabolism depends closely of Se forms and sources. Generally, organic Se has greater bioavailability and rates of tissue retention than inorganic Se (Vendeland et al, 1994;Mahan et al, 1999;Juniper et al, 2008Juniper et al, , 2011Liao et al, 2012;Speight et al, 2012). Many studies have established that selenomethionine and selenized yeast (SY) are the most appropriate source of Se for use in animal nutritional supplements because of their greater bioavailability and lower toxicity (Tinggi, 2003;Utterback et al, 2005;Wang and Xu, 2008;Skrivan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in veal, neither Se nor Se and vitamin E supplementation significantly influenced the gain and feed intake ). Dietary Se supplementation did not significantly influence growth performance in other animals species such as rabbits (Dokoupilova´et al 2007), broilers (Ahmad et al 2012;Cai et al 2012), or boars (Speight et al 2012).…”
Section: Resultsmentioning
confidence: 87%
“…straightforward movement) and resistance to oxidative stress. In another experiment crossbred boars were weaned at 28 d of age and randomly assigned to 1 of 3 dietary treatments: i) basal diets (BD) containing 0.034 mg/kg Se, BD+0.3 ppm Se as SS or BD+0.3 ppm Se as Se-Yeast and used in 3 experiments (n = 10 boars/dietary treatment) ( Speight et al, 2012a ). It was shown that Se-Yeast and SS did not affect semen quality (fresh or extended) and its fertilizing ability, while SS decreased percentage of sperm with abnormal head in comparison to BD.…”
Section: Practical Aspects Of Boar Selenium Nutritionmentioning
confidence: 99%